What We Know About Stemflow's Infiltration Area - Van Stan, John T.; Allen, Scott T. (Frontiers in Forests and Global Change, 2020)
A portion of precipitation drains to the surface down plant stems, as “stemflow.” Although, per observations to date, stemflow rarely represents >2% of gross precipitation in forests, it can result in larger water fluxes to near-stem soils that are hypothetically more important to roots. The ecohydrological importance of stemflow is often predicated upon assumptions about how it infiltrates into near-stem soils. Our objective is to review the small number of studies over the ~140 years of stemflow research that have quantified its infiltration area. We found several empirical descriptions of stemflow infiltration areas inferred from disparate approaches, and we discuss that evidence in the context of dominant assumptions and conceptualizations (i.e., equating infiltration area to basal area or estimations based on assumed soil conductivity metrics). However, we conclude that more empirical understanding of stemflow infiltration is needed before we quantify or qualify stemflow’s influence from its assumed infiltration rate. Towards this goal, we provide a critical discussion of two methods that seem most promising for quantifying stemflow infiltration area.